Deep Brain Stimulation in Anorexia Nervosa: Hope for the Hopeless or Exploitation of the Vulnerable? The Oxford Neuroethics Gold Standard Framework - Park, Rebecca J.; Singh, Ilina; Pike, Alexandra C.; Tan, Jacinta O. A. (Frontiers in Psychiatry, 2017)
Neurosurgical interventions for psychiatric disorders have a long and troubled history (1,2), but have become much more refined in the last few decades due to the rapid development of neuroimaging and robotic technologies (2). These advances have enabled the design of less invasive techniques which are more focused, such as Deep Brain Stimulation (DBS) (3). DBS involves electrode insertion into specific neural targets implicated in pathological behavior, which are then repeatedly stimulated at adjustable frequencies. DBS has been used for Parkinson’s disease and movement disorders since the 1960s (4–6), and over the last decade has been applied to treatment refractory psychiatric disorders, with some evidence of benefit in Obsessive Compulsive Disorder (OCD), major depressive disorder, and addictions (7). Recent consensus guidelines on best practice in psychiatric neurosurgery (8) stress, however, that DBS for psychiatric disorders remains at an experimental and exploratory stage. The ethics of DBS - in particular for psychiatric conditions - is debated (1,8–10). Much of this discourse surrounds the philosophical implications of competence, authenticity, personality, or identity change following neurosurgical interventions but there is a paucity of applied guidance on neuroethical best practice in psychiatric DBS, and healthcare professionals have expressed that they require more (11). This paper aims to redress this balance by providing a practical, applied neuroethical gold standard framework to guide research ethics committees, researchers, and institutional sponsors. We will describe this as applied to our protocol for a particular research trial of DBS in Severe and Enduring Anorexia Nervosa (SE-AN) (https://clinicaltrials.gov/ct2/show/NCT01924598, unique identifier NCT01924598), but believe it may have wider application to DBS in other psychiatric disorders.